Spirulina supplementation improves bone structural strength and stiffness in streptozocin-induced diabetic rats - Sophia Ogechi, Ekeuku; Pei Nee, Chong; Hor Kuan, Chan; Norazlina, Mohamed; Gabriele Ruth Anisah, Froemming; Patrick Nwabueze, Okechukwu (Elsevier Science, Ltd., 2022)
Spirulina (blue-green algae) contains a wide range of nutrients with medicinal properties which include b-carotene, chromium, and moderate amounts of vitamins B12. This study aims to determine the preventive effect of spirulina against bone fragility linked to type 2 diabetes mellitus. Thirty Sprague-Dawley rats were divided into five groups (n ¼ 6) and diabetes was induced using streptozocin. Rats with a plasma glucose level of 10 mmol/L and above were orally treated for twelve weeks with either a single dose of spirulina, metformin, or a combined dose of spirulina þ metformin per day. After the treatment, blood and bones were taken for biochemical analysis, three-dimensional imaging, 3-point biomechanical analysis, histology imaging and gene expression using qPCR. Results showed that diabetes induction and treatment with metformin caused destruction in the trabecular microarchitecture of the femur bone, reduction in serum bone marker and expression of bone formation marker genes in the experimental rats. Spirulina supplementation showed improved trabecular microarchitecture with a denser trabecular network, increased 25-OH vitamin D levels, and lowered the level of phosphate and calcium in the serum. Biomechanical tests revealed increased maximum force, stress strain, young modulus and histology images showed improvement in regular mesh and an increase in osteoblasts and osteocytes. There was an increase in the expression of bone formation marker osteocalcin. The results suggest that spirulina supplementation was more effective at improving bone structural strength and stiffness in diabetic rats compared to metformin. Spirulina may be able to prevent T2DM-related brittle bone, lowering the risk of fracture.